Neutrality of the State Civil Apparatus in the Democratic Party of Regional Head Election (Pilkada) - Al Qodar Purwo Sulistyo; Anas Santoso; Usman Usman (Universitas Negeri Semarang, 2021)
The General Election Commission of the Republic of Indonesia (KPU-RI) has determined 270 regencies / cities to hold simultaneous regional elections in 2020. With the agenda for the registration period of candidate pairs held from 4th September 2020 to 6th September 2020, and Campaign Period Stages to be held from 26th September 2020 to 5th December 2020. The direct implementation of Regional Head Election had brought changes to the culture of government at the regional level in terms of bureaucratic and political relations. The Election Hazard Index (IKP) noted that was in Regional Head Election in 2020. The neutrality problem of the State Civil Apparatus became the biggest problem, namely 167 regencies / cities out of 270 regions running the Regional Head Election (PILKADA) that was as the role of General Election Supervision (BAWASLU) Agency supervised the neutrality of the State Civil Apparatus, members of the Indonesian National Army, members of the Indonesian Police. The factors of the non-neutrality of the State Civil Apparatus were historical and socio-cultural factors, kinship relations, ambitions for career positions, ambiguous regulations (multiple interpretations), weak law enforcement, and low public awareness of legal culture. The government needed to review the Election Law regarding Civil Service Officers that minimized the occurrence of Corruption, Collusion and Nepotism in appointments and transfer of State Civil Apparatus (ASN) employees.